Management of incidental pituitary tumors - Nicholas F. Marko; Robert J. Weil (Frontiers Media S.A., 2011)
Pituitary incidentalomas are common lesions for which neurosurgical referrals may become progressively more frequent, given the increasing application of neuroimaging. The initial evaluation of a patient with radiographic evidence of an incidentaloma should focus on addressing two questions: (1) is the lesion causing neurological symptoms, and (2) is the lesion hormonally active? The answers to these two questions provide a framework for subsequent clinical management. The initial patient assessment should include a detailed history and physical examination, including the bedside assessment of visual fields. High-quality MRI imaging is essential, and formal visual field testing should be obtained in patients where the lesion abuts or compresses the optic apparatus. The initial biochemical workup is intended to assess potential pituitary hypo- or hyperfunction and should include measurement of serum levels of prolactin, insulin-like growth factor type-1, free thyroxine, testosterone, and an assessment of axis hypothalamic-pituitary-adrenal axis function. Additional testing may include serum thyroid-stimulating hormone, follicle-stimulating hormone, and luteinizing hormone levels. Neurologically-asymptomatic patients without endocrine dysfunction can be managed with observation at regular intervals, including MRI imaging at 6 months and 1 year and then annually for a period of 3 years. Follow-up biochemical assessment is not necessary in the absence of clinical symptoms or radiographic enlargement of the lesion. After 3 years the follow-up interval may be prolonged, although closer follow-up may be indicated for patients with lesions C1 cm. Most patients who either present with or who subsequently develop neurologic or endocrinologic symptoms should be considered for surgery as the first-line therapy.